Taper modeling and economic evaluation of multi-products obtained from wood of short-rotation eucalyptus stands - Menezes, Luciana da Silva; Figueredo, Joice Beatriz Lopes; Costa, Lidiomar Soares; Castro, Renato Vinícius Oliveira; Araújo Júnior, Carlos Alberto (Floresta, 2020)
This study aims at defining the appropriate model to describe the stem tapering of trees of Eucalyptus urophylla x Eucalyptus grandis hybrid, and at evaluating the economic viability of obtaining wood multi-products at different interest rates. The volume of 60 sample trees were determined, and stem tapering was described according to the models proposed by Demaerschalk, Prodan, Kozak, and Ormerod. The best model was used to convert the trees into assortments so that the wood could be optimized for the product that offers the maximum economic return with the minimum possible waste. Then, an economic viability analysis was performed for wood multi-product production, using the Net Present Value (NPV) and applying interest rates of 8 to 12% p.a. The Demaerschalk model is the most appropriate one for the study of stem tapering and assortment determination in short-rotation stands of the Eucalyptus urophylla x Eucalyptus grandis hybrid intended for multi-products in the region covered by the study. The allocation of wood for multi-products is a viable option for stands of the Eucalyptus urophylla x Eucalyptus grandis hybrid, according to the interest rates applied in the present study.